Avaliação espaço-temporal da qualidade do lixiviado do aterro sanitário de Curitiba-PR após tratamento por sistema de raízes - Ballão, Marina de Campos Rymsza (2021)
Landfills produce leachate (or slurry) throughout their lifespan and for many years after they are decommissioned. As a result, landfills become environmental liabilities that require proper management. This work evaluated the physicochemical and biological characteristics of the leachate from the Curitiba-PR Landfill, which for about 21 years received urban solid waste from the capital of Paraná and its metropolitan region. Using data from the environmental monitoring of the landfill leachate treatment system, covering the period from 2009 to 2019. Adaptations that occurred in the system over time and in the different forms of treatment considered, such as the implementation of wetlands as the final treatment step. Data analyzed by multivariate and univariate statistical treatments. It was possible to observe the significant interference in the quality of the leachate, both in the different stages of treatment and by time. From the point of view of the treatment stages, observing that the first monitoring point, equalization tank, where the leachate is raw, presented the greatest variations in values, mainly due to the closure of the landfill in 2010. From the evaluation of COD and BOD values, it was possible to verify the evolution of the landfill biodegradability index. The influence of the wetlands implementation on the quality of the final effluent verified by parameters such as BOD, COD, N-NH3, and from this evaluation, it was verified that compliance with the limits established by the legislation was possible after passing the effluent through the wetlands. Regarding the behavior of the evaluated metals, a random behavior detected both in the raw leachate and in the final effluent.